Silver nanoparticles - graphene oxide nanocomposite for antibacterial purpose - Chook, S.W.; Chia, C.H.; Zakaria, S.; Ayob, M.K.; Chee, K.L.; Neoh, H.M.; Huang, N.M. (2011)
Graphene oxide (GO) sheets, a single layer of carbon atoms which can be served as substrates for fabricating metallic nanoparticles-GO nanocomposites. In this study, the nanocomposite of silver nanoparticles and graphene oxide were produced via in-situ synthesis and with the addition of chitosan to investigate the formation of silver nanoparticles on the graphene oxide sheets. XRD and UV-Vis studies confirmed the formation of silver nanoparticles on GO sheets, while TEM and FESEM images presented the loading of silver nanoparticles on the GO sheets. The degree of loading and distribution of the silver nanoparticles on the graphene oxide were depend on the method during the formation of silver nanoparticles. The nanocomposites can be potentially used in food packaging and biomedical applications.